Le sexe du savoir - Le Doeuff, Michèle (Aubier, 1998)
Le savoir est-il l'apanage du sexe masculin? L'auteur, chargée de recherches au CNRS, fait ici la généalogie des mythes qui sexualisent le savoir et donc le pouvoir. Sur un ton polémique et drôle, elle propose un parcours original dans l'histoire de la philosophie et de la littérature, mais aussi dans l'actualité.
Keywords: approches et analyses; discipline; fem1000; genre; identités LGBTQIA2+; identités de genre; misogynie; philosophie; premier cycle; sciences humaines; sexisme; systèmes d'oppression; thématiques

The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation in the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.
Accès par ProQuest
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; atlanta; discipline; ethnographie; genre; harcèlement sexuel; masculinisme; montréal; mémoires/thèses; nouvelle-orléans; patriarcat; philosophie; périodes historiques; régions géographiques; résistance; san francisco; sciences humaines; sofia; systèmes d'oppression; thématiques; violences

L'identité féminine : biologie ou conditionnement social? - Irigaray, Luce (Femmes : moitié de la terre, moitié du pouvoir, 1994)
Keywords: 1900-1999; 1990-1999; approches et analyses; discipline; europe; fem1000; france; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppression; théories féministes

"Chapitre I".De l'assujettissement des femmes. - Mill, John Stuart (De l'assujettissement des femmes, 1992)
Première édition 1867
Keywords: 1800-1899; approches et analyses; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppression; thématiques

De l'assujettissement des femmes. - Mill, John Stuart (Avatar, 1992)
L´écrivain britannique John Stuart Mill était l´un des premiers écrivains masculins à se positionner pour l´égalité des sexes et à défendre la libération des femmes. Il se pencha sur la liberté économique des femmes et était de l´avis que le rôle d´une femme dans le mariage devait évoluer. Le livre « De l’assujettissement des femmes » est un classique de la littérature féministe. Le philosophe et politicien britannique John Stuart Mill (1806+1873) est un des penseurs libéraux les plus importants du 19e siècle. Il est particulièrement connu pour ses théories d´utilitarisme. Il s´est occupé de divers sujets politiques et philosophiques, dont les concepts de liberté et d´égalité des sexes.
Première édition 1867
Keywords: 1800-1899; approches et analyses; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppression; thématiques

Justice, gender, and the family - Okin, Susan Moller (Basic Books, 1989)
This work is a feminist critique of modern political theory. The author sets out to show how the failure to apply theories of justice to the family not only undermines democratic values but has led to a major crisis over gender-related issues.
Keywords: amériques; approches et analyses; care; discipline; division sexuelle du travail; droit; droits des femmes*; famille; genre; mariage; maternité; militance; patriarcat; philosophie; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; stéréotypes de genre; systèmes d'oppression; thématiques; travail; états-unis

Cultural feminism versus post-structuralism: The identity crisis in feminist theory - Alcoff, Linda (Signs, 1988)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; discipline; fem1000; femmes*; identités sexuelles; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppression; états-unis; études culturelles

Traité de la morale et de la politique 1693: la Liberté - Suchon, Gabrielle (Des Femmes-Antoinette Fouque, 1988)
« Vous prendrez garde, mon lecteur, qu'encore que la Morale et la Politique ne soient pas traitées en ce livre selon la méthode ordinaire des Philosophes et des Théoriciens, l'on peut néanmoins y reconnaître les principales matières de ces deux grands sujets. » Voici présenté par Gabrielle Suchon elle-même, son Traité de Morale et de Politique, publié à Lyon en 1693. Le présent ouvrage est la réédition de la première partie, la Liberté, cette « qualité savoureuse ». Avec Gabrielle Suchon, le sexe - ou, comme elle l'écrit : le Sexe - fait son entrée en philosophie. Sous sa plume, la liberté perd la figure abstraite d'un concept métaphysique pour se transformer en une question brûlante, née d'une douloureuse privation : quelle liberté pour le Sexe ? Comme le souligne Séverine Auffret, Gabrielle Suchon ne se situe pourtant pas dans une lignée féministe. Nourrie de Platon, d'Aristote et des Écritures, c'est bien dans le champ philosophique qu'elle se meut et qu'elle vient « fêter » quelque chose. Agrégée de philosophie, Séverine Auffret a entrepris de faire éditer l'oeuvre de Gabrielle Suchon (1632-1703).
Donné en lecture cours FEM1000: p.30-40;85-92;207-215
Keywords: 1600-1699; approches et analyses; discipline; discours dominant; europe; fem1000; france; philosophie; premier cycle; périodes historiques; régions géographiques; savoirs; sciences humaines; systèmes d'oppression

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppression; épistémologie